Injeksi Hormon HCG Secara Berkala Terhadap Rematurasi Induk Ikan Baung (Hemibagrus nemurus) - Isriansyah, Isriansyah; Maidie, Asfie; Agriandini, Maulina; Nurjannah, Nurjannah; Ningtias, Ismawaty Ayu; Hanif, Muhammad Wildan (Jurnal Akuakultur Sungai dan Danau, 2025)
The objectives of this experiment were to analyze the effect of periodic injection of HCG hormone on the level of egg maturity and the development of the egg diameter of green catfish (Hemibagrus nemurus), and to determine the differences in the level of egg maturity and development of egg diameter of green catfish which were injected with HCG hormone periodically with different doses. The methods used in the research were experimental method by applying injections of various doses of HCG hormone periodically (0, 100, 200, and 300 IU/kg fish body weight). The experiment was arranged using Completely Randomized Design where each treatment contained three replications. The results of this study indicate that HCG hormone injection with a dose of 300 IU/kg is not significantly different from HCG doses of 100 and 200 IU/kg (P>0.05), but significantly different from the treatment without HCG hormone injection or 0 IU/kg on the percentage of egg development with a diameter of ≥ 1 mm, the development of the egg maturity stage of the vitellogenic and the early FOM phase of female green catfish (P<0.05). Periodic HCG hormone injection is not significantly different in all treatments on the development of the final FOM phase egg maturity stage (P>0.05). The highest percentage of egg development with a diameter of ≥ 1 mm, the development of the vitellogenic and early FOM phase of egg maturity in green catfish were achieved by periodic injection of 300 IU/kg of HCG hormone.